Jealousy vs envy : European cultural background and Croatian linguistic examples = Ljubomora vs zavist : europski kulturni okvir i hrvatski jezični primjeri - Sardelić, Mirko (Array, 2021)
Speakers of many languages tend to use pairs of words such as emotion/feeling or jealousy/envy interchangeably. This paper explores the differences in the way in which the emotional states of jealousy and envy are understood (in the Croatian language ljubomora and zavist) and the influence of culture on the expression of these states. First, we establish the cultural framework that significantly shapes the experience and expression of emotional states, and summarize cognitive aspects of the two emotions. Second, we demonstrate that Croatian 19th- and 20th- century belles lettres differentiate between the two in the way it is described in sciences. Third, a psycholinguistic questionnaire was used to investigate features of the conceptual content from 209 high school students. Finally, the results were compared with the empirical corpus analysis of the linguistic constructions of emotional categories. Complementary methods used in this research show indications of an ongoing semasiological change of ljubomora and zavist in a significant part of Croatian speakers.